The association between antidepressant treatment and brain connectivity in two double-blind, placebo-controlled clinical trials: a treatment mechanism study. (August 2019) - Wang, Yun; Bernanke, Joel; Peterson, Bradley S; McGrath, Patrick; Stewart, Jonathan; Chen, Ying; Lee, Seonjoo; Wall, Melanie; Bastidas, Vanessa; Hong, Susie; Rutherford, Bret R; Hellerstein, David J; et al.
Summary: Background: Antidepressant medications offer an effective treatment for depression, yet nearly 50% of patients either do not respond or have side-effects rendering them unable to continue the course of treatment. Mechanistic studies might help advance the pharmacology of depression by identifying pathways through which treatments exert their effects. Toward this goal, we aimed to identify the effects of antidepressant treatment on neural connectivity, the relationship with symptom improvement, and to test whether these effects were reproducible across two studies. Methods: We completed two double-blind, placebo-controlled trials of SNRI antidepressant medications with MRI scans obtained before and after treatment. One was a 10-week trial of duloxetine (30–120 mg daily; mean 92·1 mg/day [SD 30·00]) and the other was a 12-week trial of desvenlafaxine (50–100 mg daily; 93·6 mg/day [16·47]). Participants consisted of adults with persistent depressive disorder. Adjusting for sex and age, we examined the effect of treatment on whole-brain functional connectivity. We also examined correlations between change in functional connectivity and improvement in symptoms of depression (24-item Hamilton Depression Rating Scale) and pain symptom severity (Symptom Checklist-90-Revised). Findings: Participants were enrolled between Jan 26, 2006, and Nov 22, 2011, for the duloxetine RCT and Aug 5, 2012, and Jan 28, 2016, for the desvenlafaxine RCT. Before and after treatment MRI scans were collected in 32 participants for the duloxetine RCT and 34 participants for the desvenlafaxine RCT. In both studies, antidepressants decreased functional connectivity compared with placebo (duloxetine study: β=−0·06; 95% CI –0·08 to –0·03; p<0·0001, ηp 2 =0·44; desvenlafaxine study: –0·06, –0·09 to –0·03; p<0·0001, ηp 2 =0·35) within a thalamo-cortico-periaqueductal network that has previously been associated with the experience of pain. Within the active drug groups, reductions in functional connectivity within this network correlated with improvements in depressive symptom severity in both studies (duloxetine study: r=0·38, 95% CI 0·01–0·65; p=0·0426; desvenlafaxine study: 0·44, 0·10–0·69; p=0·0138) and pain symptoms in the desvenlafaxine study (0·39, 0·04 to 0·65; p=0·0299). Interpretation: The findings suggest the thalamo-cortico-periaqueductal network associated with the experience of pain is a new and potentially important target for novel antidepressant therapeutics. Funding: National Mental Health Institute, Eli Lilly and Company, Pfizer Pharmaceuticals, and the Edwin S Webster Foundation.